Rediscovery and redescription of Tropidophorus micropus van lidth de jeude, 1905 (Squamata: Sauria: Scincidae) from Sarawak, east Malaysia (Borneo) - Pui, Yong Min; Das, Indraneil (Asiatic Herpetological Research Society, 2017)
Tropidophorus micropus van Lidth de Jeude, 1905, described from the upper Mahakkam River, Kalimantan, Indonesia, is here redescribed, based on new material from upper Baleh, Sarawak, East Malaysia (Borneo), collected after over 100 years. The new locality is ca. 94 km to the north of the type locality, and comprises a new national record. © 2017, Asiatic Herpetological Research Society. All rights reserved.